Aneurysm of pancreaticoduodenal arcade caused by medial arcuate ligament syndrome - case report and review of literature - Hudák, A; Guňka, I; Raupach, J; Leško, M; Krajina, A; Lojík, M (Rozhledy v chirurgii, 2021)
INTRODUCTION: Visceral artery aneurysms are rare vascular pathologies. They are usually incidental findings during the examination for other reasons. The most common clinical symptoms are nonspecific abdominal pain and bleeding caused by their rupture, with a severe clinical presentation. Aneurysms of pancreaticoduodenal arcade are more common in patients with well-developed collateral circulation due to the coeliac trunk stenosis or occlusion. CASE REPORT: In this case report the authors present a rare case of a patient with incidental finding of pancreaticoduodenal arcade aneurysm in the setting of severe stenosis of coeliac trunk origin caused by medial arcuate ligament compression. The diameter of the aneurysm was 40 mm and endovascular treatment was not possible because of unfavorable anatomical setting. The patient was successfully treated with resection of the aneurysm and the division of medial arcuate ligament during one surgery. CONCLUSION: There is no correlation between the diameter and the risk of rupture of the pancreaticoduodenal arcade aneurysm. Because of high morbidity and mortality of their rupture, most authors recommend active treatment of these aneurysms. The necessity to treat truncus coeliacus stenosis or occlusion remains a controversial issue.
Keywords: pankreas; Pancreas; Aneurysm; Celiac Artery; ligamenta; Embolization, Therapeutic; Humans; Ligaments; aneurysm − pancreaticoduodenal arcade − MALS; aneurysma; lidé; terapeutická embolizace; arteria coeliaca